Gambaran Derajat Kesehatan Ibu Hamil Kekurangan Energi Kronik Di UPTD Puskesmas Pancoran Mas Depok 2021 - Fransiska Widyanigrum; inayatul Ulya; Berliana Aullia Shaleha; Sinta Amalia Putri; Marcianus Kai Luli; Toto Kuntoro; Agustina Sari (Jurnal Kesehatan, 2022)
Chronic Energy Deficiency (KEK) is one of the problems of malnutrition during pregnancy caused by unbalanced nutritional intake, causing lack of energy for a long time. The purpose of this study was to determine the degree of public health based on the risk of Chronic Energy Deficiency (KEK) in pregnant women in the working area of ​​UPTD Pancoran Mas Health Center Depok City. This study used a quantitative descriptive method which was carried out online through google form observations (questionnaires) in October 2021 in the working area of ​​the UPTD Pancoran Mas Health Center Depok City and secondary data collection through the Depok City Health Profile, Depok City Health Office Pocket Book 2020, and several previous research journals. Data processing was carried out from secondary data (Health Profile of Depok City 2018 and Pocket Book of Depok City Health Office 2020 and other supporting journals) and primary data (questionnaire-google forms) using Microsoft Word regarding risk factors that could affect Chronic Energy Deficiency (KEK) in pregnant women in the working area of ​​UPTD Puskesmas Pancoran Mas Depok City.